Evaluating permanent deformation in asphalt rubber mixtures - Fontes, Liseane P. T. L. (2010)
Permanent deformation or rutting, one of the most important distresses in flexible pavements, has long been a problem in asphalt mixtures, mainly in countries with high temperatures such as Brazil. Throughout the years, researchers have used different test methods to estimate the rutting performance of asphalt mixtures. One of the alternatives to reduce permanent deformation in asphalt pavement layers is through the use of mixtures produced with asphalt rubber. Crumb rubber from waste tires introduced into the asphalt is one of suitable application to dispose the tires and used as an additive to enhance the properties of the conventional asphalts. This work aims at comparing the rutting performance of asphalt rubber mixtures (with dense and gap-graded aggregate gradation) with the conventional dense graded mixture most used in Brazil. The asphalt rubber mixtures were produced by the wet process using continuous blend and terminal blend asphalt rubber. To study their performance, two laboratory tests, the Repeated Simple Shear Test at Constant Height (RSST-CH) and the Accelerated Pavement Testing Simulator Test (wheel tracking) were carried out. The testing results confirmed that the use of asphalt rubber binder improves significantly the resistance to rutting. The highest resistance is presented by the mixtures produced with continuous blend binders and gap-graded aggregate gradation. The results of both testing apparatus can be correlated by a linear relationship. The testing results allowed concluding that the characteristics of the asphalt rubber binders cannot be used to predict the permanent deformation resistance of the asphalt rubber mixtures